2020
DOI: 10.1093/molbev/msaa088
|View full text |Cite
|
Sign up to set email alerts
|

Gene Duplication in the Honeybee: Patterns of DNA Methylation, Gene Expression, and Genomic Environment

Abstract: Gene duplication serves a critical role in evolutionary adaptation by providing genetic raw material to the genome. The evolution of duplicated genes may be influenced by epigenetic processes such as DNA methylation, which affects gene function in some taxa. However, the manner in which DNA methylation affects duplicated genes is not well understood. We studied duplicated genes in the honeybee Apis mellifera, an insect with a highly sophisticated social structure, to investigate whether DNA methylation was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 81 publications
2
19
0
Order By: Relevance
“…Gene body methylation, which is the most common form of DNA methylation in invertebrates, is known to be positively associated with gene expression [4]. Interestingly, duplicated genes have lower levels of gene body methylation than singletons in honeybees [99], which is consistent with the idea that DNA methylation may affect duplicate gene function. Data from plants also support the idea that divergence of gene body methylation correlates with expression divergence [100].…”
Section: Evolution and Epigenetics Of Duplicated Genessupporting
confidence: 72%
See 1 more Smart Citation
“…Gene body methylation, which is the most common form of DNA methylation in invertebrates, is known to be positively associated with gene expression [4]. Interestingly, duplicated genes have lower levels of gene body methylation than singletons in honeybees [99], which is consistent with the idea that DNA methylation may affect duplicate gene function. Data from plants also support the idea that divergence of gene body methylation correlates with expression divergence [100].…”
Section: Evolution and Epigenetics Of Duplicated Genessupporting
confidence: 72%
“…Data from other species such as zebrafish [97] are consistent with this model. Data from invertebrates and plants also support the role of DNA methylation in regulating duplicate genes [98,99]. Gene body methylation, which is the most common form of DNA methylation in invertebrates, is known to be positively associated with gene expression [4].…”
Section: Evolution and Epigenetics Of Duplicated Genesmentioning
confidence: 84%
“…Only 3 of 1456 DMGs were mapped to our previous DEGs data (Fig S2). Evidence showed that honeybee DNA methylation has an association with alternative splicing and gene duplication (Elango et al, 2009;Dyson & Goodisman, 2020), but there isn't a completely direct link between DNA methylation and gene expression. The present study and our previous study showed a same pattern that QE/2L comparison had more DMGs and DEGs than QE/ WE and WE/2L comparisons (see Fig 3 from this study and Fig 3 from Wei et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Increased copy number of 9-exon ORs may not only expand the qualitative range of compounds perceived by paper wasps, but also the quantitative olfactory space, since wasps may be able to discern unique concentration differences between CHC blends as a result of the combined action of 9-exon ORs with various response thresholds. Gene duplication can also promote regulatory diversification (Kucharski et al 2016;Dyson & Goodisman 2020). Between castes and across stages of the colony cycle, CHCs vary in P. metricus (Toth et al 2014).…”
Section: Discussionmentioning
confidence: 99%